MEKANISME INHIBISI ENZIM POLIFENOL OKSIDASE PADA SARI BUAH MARKISA DENGAN SISTEIN DAN ASAM ASKORBAT1 - Elida Mardiah (Universitas Andalas, 2011)
ABSTRACT The mechanism of polyphenol oxidase enzyme inhibition was studied by isolation of enzyme from the passion fruite juice (Passiflora Sp). The extracted enzyme polyphenol oxidase has an optimum activity at pH 5,6 and temperature of 300 C using a pirogalol substrate. The pattern of inhibition of the enzyme polifenol oxsidase studied using cysteine and ascorbic acid. Cystein of 10 mM consentration can inhibit the enzyme polyphenol oxidase activity as 97.25%, ascorbic acid with the same concentration can inhibit the enzyme polyphenol oxsidace 96.5%. The pattern of inhibition of cysteine is more likely to be competitive, while non-competitive with ascorbic acid. Keyword: polyphenol oxsidase, inhibition, cysteine, ascorbic acid